Pengaruh Customer Experience dan Perceived Ease of Use terhadap Customer Loyalty Melalui Satisfaction (Studi pada Pengguna GoFood di Aplikasi Gojek) - Aida Putri Nur Sa’adah; Tias Andarini Indarwati (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study is motivated by the increasing use of online food delivery services, which is accompanied by indications of declining user loyalty toward GoFood. The objective of this study is to analyze the effect of customer experience and perceived ease of use on customer loyalty, with satisfaction as a mediating variable. This study employs a quantitative approach with a causal research design conducted in Surabaya, involving 145 GoFood users selected through purposive sampling. Data were collected using a questionnaire based on a 5-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that customer experience and perceived ease of use have a positive and significant effect on satisfaction, which in turn has a positive effect on customer loyalty. Furthermore, satisfaction is proven to mediate the relationship between both variables and customer loyalty, while perceived ease of use does not have a direct effect on customer loyalty. In conclusion, customer satisfaction plays a crucial role in building user loyalty. Therefore, companies are recommended to enhance user experience and ease of use to strengthen customer satisfaction and loyalty toward GoFood. This study is still limited to the use of quantitative methods and only focuses on one online food delivery platform, so further research is recommended to use a mixed methods approach and involve several digital service platforms to obtain a comprehensive understanding of user loyalty behavior.